Repairing tRNA termini: News from the 3' end. Issue 12 (1st December 2016) - Rammelt, Christiane; Rossmanith, Walter
ABSTRACT: The removal of transcriptional 5′ and 3′ extensions is an essential step in tRNA biogenesis. In some bacteria, tRNA 5′- and 3′-end maturation require no further steps, because all their genes encode the full tRNA sequence. Often however, the ends are incomplete, and additional maturation, repair or editing steps are needed. In all Eukarya, but also many Archaea and Bacteria, e.g., the universal 3′-terminal CCA is not encoded and has to be added by the CCA-adding enzyme. Apart from such widespread "repair/maturation" processes, tRNA genes in some cases apparently cannot give rise to intact, functional tRNA molecules without further, more specific end repair or editing. Interestingly, the responsible enzymes as far as identified appear to be polymerases usually involved in regular tRNA repair after damage. Alternatively, enzymes are recruited from other non-tRNA pathways; e.g., in animal mitochondria, poly(A) polymerase plays a crucial role in the 3′-end repair/editing of tRNAs. While these repair/editing pathways apparently allowed peculiar tRNA-gene overlaps or mismatching mutations in the acceptor stem to become genetically fixed in some present-day organisms, they may have also driven some global changes in tRNA maturation on a greater evolutionary scale.